Kepemimpinan Transformasional dan Keterikatan Karyawan: Analisis Peran Mediasi Motivasi Intrinsik - Casimiro Soares; Arlindo do Ceu Fatima (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The changing dynamics of organizations in the digital era present challenges in meeting the growing need for effective leadership, particularly in strengthening intrinsic motivation and employee engagement. This study aims to analyze the effect of transformational leadership on employee engagement with intrinsic motivation as a mediator in private and public sector organizations in Indonesia. The research design employed a quantitative cross-sectional survey approach involving 100–150 respondents, with data analysis conducted using Structural Equation Modeling (SEM) with AMOS. The findings reveal that transformational leadership significantly enhances intrinsic motivation and employee engagement, as well as strengthens their relationship through the mediating effect of intrinsic motivation. However, the study also identified nonsignificant pathways in certain contexts, highlighting the importance of organizational contextual factors. These findings reinforce the relevance of integrating transformational leadership theory and Self-Determination Theory in explaining the psychological mechanisms of human resource development. Practically, this study implies that transformative leadership development strategies oriented toward fulfilling basic psychological needs (autonomy, competence, relatedness) are more effective in fostering emotional involvement, loyalty, and employee productivity. Furthermore, the study emphasizes the importance of designing leadership training programs and human resource management policies that focus on employee empowerment and well-being, rather than solely on organizational targets. The limitations of this research lie in its cross-sectional design and reliance on self-reported data, providing opportunities for future longitudinal and mixed-methods studies to offer a more comprehensive understanding.